Influence of soft tissue augmentation procedures around dental implants on marginal bone level changes—A systematic review. (12th October 2021) - Fickl, Stefan; Therese Kröger, Annika; Dietrich, Thomas; Kebschull, Moritz
Abstract: Objectives: This systematic review assessed the influence of soft tissue augmentation procedures on marginal bone level changes in partial or fully edentulous patients. Material and Methods: We identified three relevant PICO questions related to soft tissue augmentation procedures and conducted a systematic search of four major electronic databases for clinical studies in systemically healthy patients receiving at least one dental implant and a minimum follow‐up of one year after implant placement. The primary outcome was mean difference in marginal bone levels, and secondary outcomes were clinical and patient‐related outcomes such as thickness of peri‐implant mucosa, bleeding indices, and Pink Esthetic Score. Results: We identified 20 publications reporting on 16 relevant comparisons. Studies varied considerably and thus only two meta‐analyses could be performed. This systematic review showed that: Soft tissue augmentation either for augmentation of keratinized mucosa or soft tissue volume inconsistently had an effect on marginal bone level changes when compared to no soft tissue augmentation, but consistently improved secondary outcomes. The combination soft and hard tissue augmentation showed no statistically significant difference in terms of marginal bone level changes when compared to hard tissue augmentation alone, but resulted in less marginal soft tissue recession as shown by a meta‐analysis. Soft or hard tissue augmentation performed as contour augmentations resulted in comparable marginal bone level changes. Conclusions: Peri‐implant soft and hard tissues seem to have a bidirectional relationship: " Bone stands hard, but soft tissue is the guard ".